PENGARUH CUSTOMER VALUE TERHADAP LOYALITAS PELANGGAN CAFE RELOAD KITCHEN KOTA PALEMBANG - Veliano Denise Watak; Muhammad Wadud; Azra’ie K. Rosni (Universitas Indo Global Mandiri)
This research is conducted to determine the effect of customer value on customer loyalty at Reload Kitchen Cafe Palembang. It is carried out based on both qualitative and quantitative methods. The independent variable in this research is customer value and the dependent variable is customer loyalty. The techniques of data collection in this research include interviews, observation, and questionnaires. The data used are primary and secondary data. The analisys using SPSS program version 22. They are analyzed by using simple regression analysis method and t-test. The result of the study shows that customer value has significant effect to customer loyalty. The value of R is 0.825. It means there is a strong relationship between customer value and customer loyalty. The result of this research is reinforced by the result of hypothesis testing. T-Test shows a significance level of 0,000 greater than 0,05 which means customer value affects the customer loyalty at Reload Kitchen Café.Keywords: Customer Value, Customer Loyalt, Marketing